1974
DOI: 10.2118/4143-pa
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature-Oxidation Reaction Kinetics and Effects on the In-Situ Combustion Process

Abstract: The kinetics of low-temperature oxidation (LTO) of crude oils in porous media was studied. Isothermal integral reactor data were analyzed to obtain rate equations for the over-all rate of the partial oxidation reactions at temperatures below partial oxidation reactions at temperatures below 500 deg. F. The reaction order with respect to oxygen was found to be between 0.5 and 1.0. The order of the reaction was dependent upon the crude but independent of the properties of the porous medium. The activation energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 0 publications
3
60
0
Order By: Relevance
“…Alexander et d( 1962) and Al-Saadon (1970) showed that fuel availability was increased when LTO of crude oil took place. Dabbous and Fulton (1974) corroborated this and also found that LTO causes a substantial decline in recoverable oil from the distillation and cracking zones, an increase in the fuel deposition and marked changes in the fuel characteristics and coked sand properties. Weijdema (1968) and Fassihi (198 1) found that the order for the LTO reaction, in terms of the partial pressure of oxygen, was close to unity.…”
supporting
confidence: 73%
“…Alexander et d( 1962) and Al-Saadon (1970) showed that fuel availability was increased when LTO of crude oil took place. Dabbous and Fulton (1974) corroborated this and also found that LTO causes a substantial decline in recoverable oil from the distillation and cracking zones, an increase in the fuel deposition and marked changes in the fuel characteristics and coked sand properties. Weijdema (1968) and Fassihi (198 1) found that the order for the LTO reaction, in terms of the partial pressure of oxygen, was close to unity.…”
supporting
confidence: 73%
“…It has been shown that LTO reaction increases the amount of fuel available for combustion (Alexender et al, 196;A1-Saadon, 1970) and causes a substantial decline in recoverable oil from the distillation and cracking zones (Dabbous and Fulton, 1974), Low air fluxes in the oxidation zone resulting from reservoir heterogeneities and oxygen channeling promote LTO reactions. Poor combustion characteristics of the crude also tend to promote LTO due to low oxygen consumption.…”
Section: Low Temperaturementioning
confidence: 99%
“…Some investigators (Dabbous et al, 1974;Lin et al, 1984) found that the combustion reaction was diffusion controlled, while others found it to be chemical reaction controlled (Hughes et al, 1987;Fassihi and Brigham, 1982;. Islam et al, 1989, contend that the laboratory experiments are almost always conducted under rather ideal conditions, and the experiments conducted under such ideal situations permit oxygen interracial mass transfer rate to be quite high and thus likely to mask the influence of diffusion on the combustion reactions in the reservoir.…”
Section: High Temperature Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cram and Redford (1977), Dietz (1 970), Dietz and Weidjema (1 968), Morse (1 976), Nelson and McNiels (1956), Showalter (1963), Smith and Perkins (1973), Reed et al (1960), andWalter (1977). The performance of in situ combustion processes depends on the accompanying low-temperature oxidation (LTO) reactions (Alexander et al, 1962;Dabbous and Fulton, 1974;Burger and Sahuquet, 1973). Furthermore, results of published laboratory and field studies indicate that more meaningful analysis of combustion data cannot be made until the LTO reaction kinetics are studied and the reaction mechanisms elucidated.…”
mentioning
confidence: 99%